2010
DOI: 10.1002/ejlt.201000048
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface analysis of the lipid‐discharging obligate hydrocarbonoclastic species of the genus Alcanivorax

Abstract: This study presents novel information useful for addressing the question how species of the genus Alcanivorax discharge triacylglycerols (TAG) and/or wax esters (WE). The observed structures were referred as ''blebs'' according to Gauthier et al. [1] to avoid confusion with other discharging phenomena. The cells were aerobically cultivated on solid media and not in liquid media to maintain the cells in the native state, and were investigated by transmission electron microscopic (TEM) and scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Importantly, we were able to observe the bio-surfactant vesicles (spherical particles with ca. 150 nm diameter) which are produced by A. borkumensis to ensure the effective emulsification of oil in seawater [26]. This finding confirms that the PAH-MNPs coating is attached reversibly and does not prevent the formation and discharge of the vehicles.…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 56%
See 1 more Smart Citation
“…Importantly, we were able to observe the bio-surfactant vesicles (spherical particles with ca. 150 nm diameter) which are produced by A. borkumensis to ensure the effective emulsification of oil in seawater [26]. This finding confirms that the PAH-MNPs coating is attached reversibly and does not prevent the formation and discharge of the vehicles.…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 56%
“…Cell surface engineering with polycation-coated magnetic nanoparticles is a fast and straightforward process utilizing the direct deposition of positively charged iron oxide nanoparticles onto microbial cells during a brief incubation in excessive concentrations of nanoparticles. 20 Here we have chosen A. borkumensis rod-shaped halophilic bacteria (Figure 1a,b) as a target microorganism for cell surface engineering with magnetic nanoparticles for the following reasons: (1) these hydrocarbonoclastic 27 bacteria are regarded as an important tool in marine oil spill remediation 26 and potentially can be used in industrial oil-processing bioreactors, therefore the external magnetic manipulations with these cells seems to be practically relevant; (2) A. borkumensis are marine Gramnegative species (Figure 1 c) having relatively fragile and thin cell walls, unlike the previously coated soil bacteria, 20 fungi 36 and freshwater algae cells. 18 Consequently, the deposition of nanoparticles should be performed with extreme care to ensure the survival of magnetized cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In fed-batch cultures with constant substrate feeding of sodium acetate as sole carbon source, cell densities of up to about 20 g/L were obtained using A. borkumensis SK2 (Manilla-Pérez et al, unpublished observations). In addition, studies showed that A. borkumensis SK2 and A. jadensis T9 discharge TAG and WE by blebs which are formations similar to outer membrane vesicles [31]. This could be another advantage if these bacteria are used to produce neutral lipids biotechnologically.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic studies of A. borkumensis have found an upregulation of glycoprotein regulation and transport genes in the presence of hydrocarbons. 15,30 A ∼25 h increase in lag time during cell culture may stem from the time required for gene regulation leading to biosurfactant production and access to oil as an energy source. 31 Note that cells cultured with hexadecane are smaller than those cultured with organic carbon, which has been reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…Alcanivorax borkumensis (A. borkumensis) is a Gram-negative bacterium that is capable of degrading n - and branched-alkanes. , This bacterium dominates bacterial communities around oil spills and it synthesizes two forms of an anionic glycoprotein surfactant. , One form is glycine-free and is released in the death phase of bacterial growth from the interface. The second, cell membrane-bound form contains glycine and reports suggest that it increases cell hydrophobicity. , A.…”
Section: Introductionmentioning
confidence: 99%